2013
DOI: 10.1016/j.bone.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural patterns of the proximal femur in relation to age and hip fracture risk in women

Abstract: Fractures of the proximal femur are the most devastating outcome of osteoporosis. It is generally understood that age-related changes in hip structure confer increased risk, but there have been few explicit comparisons of such changes in healthy subjects to those with hip fracture. In this study, we used quantitative computed tomography and tensor-based morphometry (TBM) to identify three-dimensional internal structural patterns of the proximal femur associated with age and with incident hip fracture. A popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…In this study, we applied statistical multiparametric mapping to investigate spatial differences in proximal femoral density and cortical bone properties between two major types of hip fracture—femoral neck and trochanteric fracture—and healthy controls. In contrast to previous studies, we identified acute hip fracture–related features with both VBM of vBMD and SPM of cortical bone properties, thus providing a more comprehensive QCT assessment of the proximal femur. Investigated features included vBMD, Ct.Th, Ct.vBMD, and EndoTb.vBMD.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, we applied statistical multiparametric mapping to investigate spatial differences in proximal femoral density and cortical bone properties between two major types of hip fracture—femoral neck and trochanteric fracture—and healthy controls. In contrast to previous studies, we identified acute hip fracture–related features with both VBM of vBMD and SPM of cortical bone properties, thus providing a more comprehensive QCT assessment of the proximal femur. Investigated features included vBMD, Ct.Th, Ct.vBMD, and EndoTb.vBMD.…”
Section: Discussionmentioning
confidence: 90%
“…Various clinical studies have demonstrated that hip fracture is affected by anthropometric parameters, bone quality (Haider et al, 2013), proximal femur anatomy (Carballido-Gamio et al, 2013;Gregory and Aspden, 2008;Ito et al, 2010;Park et al, 2014), cortical thickness (Long et al, 2015;Loveridge et al, 2010), hip soft tissue thickness (STT) (Majumder et al, 2007(Majumder et al, , 2008(Majumder et al, , 2013, landing surface (Baddoura et al, 2011;Van der Zijden et al, 2012), etc. All these parameters are subject dependent as they vary with gender, race, ethnicity and age (Peacock et al, 2009;Wang et al, 1994;Zhuang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ordinary clinical computed tomography (CT) scans have been be used to identify focal 3D bone loss in ageing and as a predictor of fracture [11], [12], [13], [14], [15], [16]. Cortical Bone Mapping (CBM) couples CT imaging capability with an evaluation method to find average differences between groups known as statistical parametric mapping (SPM) [11], [12], [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cortical Bone Mapping (CBM) couples CT imaging capability with an evaluation method to find average differences between groups known as statistical parametric mapping (SPM) [11], [12], [13], [14], [15], [16]. CBM can also be used to visualise femoral cortical thickness in CT scans from individual patients (Fig.…”
Section: Introductionmentioning
confidence: 99%